DESIDOC JOURNAL OF LIBRARY AND INFORMATION TECHNOLOGY: A BIBLIOMETRIC ANALYSIS (International Journal of Food and Nutritional Sciences, 2022)
The present study provides detailed bibliometric investigation of 267 articles published in DESIDOC Journal of Library and Information Technology (DJLIT) during the period 2018-2022. The study analyses the various bibliometric parameters such as, chronological distribution of articles and references, geographical distribution, distribution of Intellectual output, and pagination pattern. DESIDOC Journal of Library and Information Technology (DJLIT) is one of the most popularjournals of library and information science being published in India. It is brought out by Defence Scientific Information and Documentation Centre (DESIDOC), a constituent establishment of Defence Research and Development Organisation (DRDO). DJLIT has completed 30 years of its publication in 2021. This paper presents bibliometric analyses of DJLIT during 2018-2022. The analysis covers various parameters like growth pattern, content coverage, authorship patterns, subjectwise distribution of articles, etc